PENGARUH PERCEIVED VALUE, CORPORATE IMAGE, PRICE FAIRNESS, SALESPEOPLE TERHADAP INTENTION TO BUY PREMI ASURANSI BUMIPUTRA (Dengan Attitude Sebagai Variabel Mediasi, Informasi Sebagai Variabel Moderasi) - Nina Adelina; Hidup Marsudi (STIE Atma Bhakti, 2021)
In this study the decision to buy a life insurance policy AJB Bumiputera 1912. This is due to the company's inability to add new customers. So it is important to research what a person is buying an insurance for. It is also important in this study to provide input to AJB Bumiputera 1912 in an effort to determine an effective strategy related to determining the decision variables are considered by AJB Bumiputera 1912 life insurance customers to purchase a life insurance policy. The scope of this research is the intention of the solo community in buying AJB Bumiputera 1912 life insurance products. This research takes place in city of Surakarta. This research is an explanatory type, namely a causal relationship with four independent variables, namely perceived value, fairness of price, company image, and sales force with purchasing decisions as the dependent variable. Attitude towards insurance is the mediating variable and information is the moderating variable in this study. This research is a cross sectional study which relies on data that occurs at one point. So that the constructed model is not designed to capture changes that occur over several points in time. For this reason, in order for this research to be generalized, it is necessary to examine the changing external factors that can affect the construction of the model.